Water sorption and solubility of different calcium hydroxide cements (Journal of Applied Oral Science, 2009)
OBJECTIVES: Calcium hydroxide cements have been largely used in deep cavities due to their abilities to stimulate dentin formation. However, their resistance can be relatively low and their solubility relatively high, in many instances. This study evaluated water sorption and solubility of different calcium hydroxide cements, in order to show alterations that may reduce their effectiveness. MATERIAL AND METHODS: Five discs (20 mm in diameter and 1.5 mm thick) of three different materials (Biocal®, Dycal® and Hidro C®) were prepared with the aid of a ring-shaped metallic matrix. After being stored at 37ºC for 24 h, the discs were weighed on a precision weight scale, dehydrated and weighed again. Immediately after weighing, discs were stored for a week in 50 mL of distilled water at 37ºC and, then, weighed again, dehydrated and submitted to a new weighing. The loss of soluble material and its water sorption was obtained from the difference between the initial and the final dry mass of each disc, after 1 week of immersion in water. Data were analyzed for significant differences by two-way ANOVA and Tukey's test (p